Chaotic System-based Pseudo Random Bit Generator and Post-processor Design for Image Encryption - Karakaya, Baris (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper presents an implementation of both continuous and discrete time chaotic system-based pseudo random bit generation by using three dimensional Lorenz system and one dimensional Logistic map. As chaotic systems are preferred in random number generator applications, two different chaotic systems are used as entropy source in the proposed design to make the design more secure. The electronic circuit equivalences of chaotic systems are designed and simulated in Orcad-Pspice environment to obtain values of state variables in fractional number format and input to proposed post-processor algorithm. The generated random bit stream is tested by using NIST 800.22 statistical test suite to demonstrate the randomness of proposed system statistically. Also, an image encryption application is executed using pseudo random bit stream. The results of statistical tests and image encryption show that the proposed pseudo random bit generator design is suitable and can be preferred in secure image or media transmission systems. © 2022 IEEE.
13th National Conference with International Participation, ELECTRONICA 2022 -- 19 May 2022 through 20 May 2022 -- Sofia -- 182635
Keywords: chaos; image encryption; post-processor; pseudo random bit; statistical tests